Determinants of academic law libraries' use, collections, and services among the faculty members: a case study of University of Peshawar. Issue 4 (5th October 2015) - Khan, Ghalib; Bhatti, Rubina
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the determinants of academic law libraries' use, collections and services among the faculty members of the University of Peshawar, Khyber Pakhtunkhwa, Pakistan. Design/methodology/approach – Keeping in view the objectives of the study, a survey based on a well-structured questionnaire was designed to collect data about law libraries' usage, collection and services from the faculty members of 19 law colleges, including Law College, University of Peshawar, and 18 affiliated law colleges situated in the different geographical location of the province of Khyber Pakhtunkhwa, Pakistan. Findings – Results of the study indicate that most of the faculty members use law libraries for the issue and return of books and consult textbooks for their teaching and other academic activities. The overall results show the usage, collections and services of law libraries as somehow satisfactory. Research limitations/implications – The scope of this paper covers constituent college of the University of Peshawar and its 18 affiliated law colleges (Total 19), and the geographical area is restricted to the province of Khyber Pakhtunkhwa. The scope of this paper can be extended to additional private and public sector universities in Pakistan, as well as abroad. Originality/value – There are number of studies on the usage, collections and different library services, but this study is the first of its kind in Pakistan, specifically focusing on academic law libraries at a provincial level. This study will pave way to fulfill the demands of law faculty members and legal practitioners teaching in the legal institution of Pakistan.